A Randomized, Placebo-Controlled Trial Assessing the Effect of VISBIOME ES Probiotic in People With HIV on Antiretroviral Therapy. (7th December 2021) - Presti, Rachel M; Yeh, Eunice; Williams, Brett; Landay, Alan; Jacobson, Jeffrey M; Wilson, Cara; Fichtenbaum, Carl J; Utay, Netanya S; Dube, Michael P; Klingman, Karin L; Estes, Jacob D; Flynn, Jacob K; et al.
Abstract: Background: A5350, a phase II, randomized, double-blind study, evaluated the safety and tolerability of the probiotic Visbiome Extra Strength (ES) over 24 weeks and measured effects on inflammation and intestinal barrier function. Methods: The primary outcome was change in soluble CD14 (sCD14) levels; secondary outcomes included safety and tolerability, markers of inflammation and cellular activation, and microbiome. In a substudy, gut permeability was assessed by paired colonic biopsies measuring the area of lamina propria occupied by CD4+ cells, interleukin (IL)-17+ cells, and myeloperoxidase (MPO). Changes between arms were compared with the 2-sample t test with equal variance or the Wilcoxon rank-sum test. For safety, the highest graded adverse events (AEs) were compared between arms using the Fisher exact test. Results: Overall, 93 participants enrolled: 86% male, median age 51 years, median CD4 count 712 cells/mm3. Visbiome ES was safe and well tolerated. There was no difference in mean change in sCD14 from baseline to week 25/26 between placebo (mean change, 92.3 µg/L; 95% CI, –48.5 to 233 µg/L) and Visbiome ES (mean change, 41.0 µg/L; 95% CI, –94.1 to 176.2 µg/L; P =.60). Similarly, no statistically significant differences between arms in inflammatory marker changes were identified. In substudy participants, no statistical differences between arms for change in cellular marker expression or gut permeability were observed ( P >.05 for all). The microbiome demonstrated increased probiotic species and a significant decrease in Gammaproteobacteria ( P =.044) in the Visbiome ES arm. Conclusions: Visbiome ES was safe and altered the microbiome but demonstrated no effect on systemic inflammatory markers, pathology, or gut permeability in antiretroviral therapy–treated people with HIV.